2024
DOI: 10.7150/ijbs.89568
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TGF-β/SMAD Signaling in Hepatocellular Carcinoma: from Mechanism to Therapy and Prognosis

Xin Xin,
Xiyu Cheng,
Fanxin Zeng
et al.

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide, with high incidence and mortality, accounting for approximately 90% of liver cancer. The development of HCC is a complex process involving the abnormal activation or inactivation of multiple signaling pathways. Transforming growth factor-β (TGF-β)/Small mothers against decapentaplegic (SMAD) signaling pathway regulates the development of HCC. TGF-β activates intracellular SMADs protein through membrane receptors, resulting in a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Prior research demonstrated that TGF-β promoted HCC growth, invasion, immune evasion, and ECM deposition. 58 Galunisertib, a TGF-β inhibitor, showed promise in slowing advanced HCC development. 59 Combining TGF-β targeting drugs in the future could inhibit HCC proliferation and immune evasion by reducing TGF-β expression, and concurrently down-regulate Sema3C expression to enhance efficacy in reducing drug resistance and preventing tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research demonstrated that TGF-β promoted HCC growth, invasion, immune evasion, and ECM deposition. 58 Galunisertib, a TGF-β inhibitor, showed promise in slowing advanced HCC development. 59 Combining TGF-β targeting drugs in the future could inhibit HCC proliferation and immune evasion by reducing TGF-β expression, and concurrently down-regulate Sema3C expression to enhance efficacy in reducing drug resistance and preventing tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β pathway plays a crucial role in the progression of HBV-associated HCC. Many drugs targeting the TGF-β pathway have shown promising results in treating HCC ( 164 ). However, the clinical applicability and efficacy of these treatments require further validation through extensive clinical trials.…”
Section: Tgf-βmentioning
confidence: 99%